Abdominal profiles of Icelandic Pink-footed Geese Anser brachyrhynchus in spring - Boyd, H; Fox, A D (Wildfowl, 1995)
Pink-footed Geese in Scotland in mid-April had larger median abdominal profiles than those newly arrived at a lowland staging area in southwest Iceland in the second half of April. Their profiles returned to Scottish levels within about ten days of arrival and continued to increase until about 10 May, when many geese were leaving for their breeding places. Unpaired adults and those less than a year old had smaller profiles than paired adults, both before and after migrating. paired females had larger profiles than their mates. In Iceland, females in isolated pairs or small groups tended to have larger profiles than those still in large flocks. The small numbers of paired females feeding on newly-tilled ground in Scotland and on rough pastures in Iceland tended to have smaller profiles than the majority feeding on improved grasslands in both countries. Increases in profiles in Iceland were directly associated with rising daily temperatures, which affected both the rate of snowmelt and the early growth of food plants. Annual breeding success (as measured by mean brood-size and the proportion of young found in Scotland in the autumn) was correlated significantly with differences in the median profiles of females and males in the previous early May. Although less informative about causation than detailed analyses of the body composition of dead geese, or repeated observations of changes in the profiles of individually identifiable live birds, scanning the profiles of relatively large numbers of unmarked geese yields results consistent with those from more intensive studies. This can help to decide which questions to ask about changes in the body condition of geese through the year, and their relationship to survival and breeding success.